2022
DOI: 10.3390/nu14132670
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Restriction Improves Metabolic Dysfunction in Patients with Metabolic Syndrome in a Randomized, Controlled Trial

Abstract: Dietary restriction (DR) reduces adiposity and improves metabolism in patients with one or more symptoms of metabolic syndrome. Nonetheless, it remains elusive whether the benefits of DR in humans are mediated by calorie or nutrient restriction. This study was conducted to determine whether isocaloric dietary protein restriction is sufficient to confer the beneficial effects of dietary restriction in patients with metabolic syndrome. We performed a prospective, randomized controlled dietary intervention under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…Recently it has become clear that the macronutrient composition of the diet is a key factor in the “food as medicine” approach to health (Green and Lamming, 2021). Multiple studies have highlighted dietary protein as a key determinant of human health (Ferraz-Bannitz et al ., 2022; Fontana et al ., 2016; Lagiou et al, 2007; Levine et al, 2014; Sluijs et al, 2010; Vergnaud et al, 2013). In animals as well, dietary protein has identified as a key regulator of metabolic health as well as longevity (Solon-Biet et al ., 2014; Solon-Biet et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has become clear that the macronutrient composition of the diet is a key factor in the “food as medicine” approach to health (Green and Lamming, 2021). Multiple studies have highlighted dietary protein as a key determinant of human health (Ferraz-Bannitz et al ., 2022; Fontana et al ., 2016; Lagiou et al, 2007; Levine et al, 2014; Sluijs et al, 2010; Vergnaud et al, 2013). In animals as well, dietary protein has identified as a key regulator of metabolic health as well as longevity (Solon-Biet et al ., 2014; Solon-Biet et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary composition has a strong influence on longevity and health. Multiple short term randomized clinical trials of protein restriction (PR) show that PR improves multiple markers of metabolic health, reducing adiposity and improved insulin sensitivity (Ferraz-Bannitz et al, 2022; Fontana et al, 2016). In rodents, PR improves metabolic health, and the consumption of low protein (LP) diets promotes longevity (Green and Lamming, 2019; Green et al, 2022; Laeger et al, 2014; Richardson et al, 2021; Solon-Biet et al, 2014; Speakman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In model organisms and humans, dietary protein is a critical regulator of a wide variety of biological processes that determine metabolic health and lifespan (Trautman et al, 2022). Low protein diets promote healthspan and lifespan in flies and rodents (Fontana et al, 2016; Hill et al, 2022a; Solon-Biet et al, 2014), and emerging data suggests the same may be true for humans (Ferraz-Bannitz et al, 2022; Fontana et al, 2016; Laeger et al, 2014; Levine et al, 2014; Mair et al, 2005; Yu et al, 2020). Paradoxically, while consumption of additional protein is recommended as a way of supporting muscle growth and strength gains during resistance exercise training, there is also evidence that high protein diets result in detrimental health effects (Lagiou et al, 2012; Mittendorfer et al, 2020; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the long-standing idea that “a calorie is a calorie,” research over the last two decades has shown that calories from different macronutrient sources have distinct impacts on health (Hall et al, 2015). Dietary protein in particular has been shown to have a critical role in the regulation of metabolic health and longevity; low protein diets are associated with reduced rates of diabetes and other age related diseases in human longitudinal studies, and promote leanness and insulin sensitivity in human randomized clinical trials (Ferraz-Bannitz et al, 2022; Fontana et al, 2016; Levine et al, 2014; Sluijs et al, 2010). In mice, low protein, high carbohydrate diets promote leanness, glucose tolerance, and extend lifespan (Hill et al, 2022b; Richardson et al, 2021; Solon-Biet et al, 2014; Solon-Biet et al, 2015); many of the benefits of a low protein diet are mediated by reduced consumption of the branched-chain amino acids (BCAAs), particularly isoleucine and valine, and we have recently shown dietary histidine is also associated with increased adiposity and body mass index (BMI) (Flores et al, 2022; Green et al, 2022b; Jang et al, 2016; Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the PR diet considerably improved physical parameters, blood glucose and lipid levels, energy expenditure, and insulin sensitivity in patients suffering from obesity and MetS. 146 Additionally, studies on patients with obesity have demonstrated that a high protein intake during weight loss impairs insulin signaling in muscles and normal glucose uptake rates. 147 Maintaining a low protein intake can ensure efficient weight loss outcomes and glycemic management among patients with obesity.…”
Section: Dietary Patterns With Potential For Cardiometabolic Healthmentioning
confidence: 99%